Epidemiologi temporal dan spasial ehrlichiosis monositik anjing di Nueva Ecija, Filipina - Francis Y. Reyes; Christian C. Santos; Armando G. Agustin (ARSHI Veterinary Letters, 2025)
Canine monocytic ehrlichiosis (CME) is a vector-borne disease that affects dogs. This study characterized CME epidemiological profiles by examining associations with age, sex, breed, clinical manifestations, acaricide use, and case distribution in veterinary clinics in Nueva Ecija, Philippines. A total of 1,117 CME-positive cases were collected from eight clinics in Cabanatuan, Muñoz, San Jose, and Gapan City between 2021 and 2022. Diagnosis used commercial rapid test kits. Statistical analyses revealed significant associations between CME prevalence and age, breed, and patient demographics. Cabanatuan City reported the highest number of cases (n = 508). Sex and seasonal variation showed no significant associations with CME occurrence, although cases increased during the hot months (March–June).